"A Comparison of Outcomes between Lichtensteinand Laparoscopic Transabdominal Preperitoneal Hernioplasty for Recurrent Inguinal Hernia". Issue 11 (November 2018) - Yang, Bin; Zhou, Shengning; Li, Yingru; Tan, Jianan; Chen, Shuang; Han, Fanghai
There remain concerns about the optimal technique for repairing recurrent inguinal hernias because of the high risks of complications and recurrence. The aim of this study was to compare Lichtenstein hernioplasty with the transabdominal preperitoneal (TAPP) laparoscopic technique in the treatment of recurrent inguinal hernias. One hundred twenty-two patients who underwent surgery for recurrent inguinal hernia were prospectively randomized to receive either Lichtenstein (n = 63) or TAPP (n = 59) hernioplasty between January 2010 and December 2014. Baseline characteristics, intraoperative complications, and short- and long-term postoperative factors were evaluated. Preoperative factors were comparable between the two groups. The average follow-up period was 46.2 ± 8.5 months. The two groups had similar intraoperative and short-term postoperative complication rates, whereas the rate of long-term postoperative complications was lower for the TAPP group than the Lichtenstein group (6.8% vs 23.8%, respectively, P = 0.012). The TAPP group had significantly lower visual analogue scale scores, fewer analgesics consumption, and faster recovery than the Lichtenstein group ( P < 0.05). Chronic pain was more prevalent in the Lichtenstein group than the TAPP group (15.9% vs 3.4%, respectively, P = 0.031). The recurrence rate was 4.8 per cent for the Lichtenstein group and 1.7 per cent for the TAPP group, with no significant difference ( P = 0.62). Both the Lichtenstein and TAPP procedures are safe and effective methods for repairing recurrent inguinal hernia with low incidence rates of life-threatening complications and recurrence. The TAPP procedure is superior to the Lichtenstein repair in terms of reduced postoperative pain, shorter sick leave, faster recovery, and better cosmetic results. Careful selection of the surgical procedures and implementation of technical essentials are necessary.